Developing thresholds of potential concern for invasive alien species: Hypotheses and concepts - Llewellyn C. Foxcroft (Koedoe: African Protected Area Conservation and Science, 2009)
The Kruger National Park (KNP) has developed and refined a system of management called ‘strategic adaptive management’ (SAM), which rests on the concept of ‘threshold of potential concern’ (TPC). TPCs represent end-points in a continuum of change. When thresholds are reached – at which point concerns of negative impacts on biodiversity are raised – management options are explicitly considered and implemented. This paper describes the TPCs developed for monitoring and managing invasive alien species (IAS). More importantly, however, it describes the conceptual understanding, principles and hypotheses adopted as the foundations for setting these TPCs. In accordance with adaptive management practices, the TPCs will be revised as the ecological and conceptual understanding of invasions grows and information is gained through research in the KNP and elsewhere. Conservation implication: In accepting that species and systems are variable, and that flux is inevitable and desirable, these TPCs developed for invasive alien species specifi cally, provide end points against which monitoring can be assessed. Once a threshold is reached, the cause of the threshold being exceeded is examined and management interventions recommended.